The Influence of Introductory Coursework on Preservice Teachers’ Sense of Self-efficacy Towards Teaching in an Inclusive Classroom - Smothers, Moriah; Colson, Tori; Yssel, Nina; Taylor, Linda (Journal of the American Academy of Special Education Professionals, 2020)
Since the majority of students receiving special education services spend most of their school day in the general education classroom (Kena et al., 2015), it is imperative that teacher preparation programs equip preservice teachers for that context. This quantitative study explored the influence a single introductory special education course had on the efficacy beliefs of preservice teachers towards teaching in an inclusive classroom. The study included 100 participants that were undergraduate students enrolled in an introduction to special education course. Students were given the Teacher Efficacy for Inclusive Practices survey (Sharma, Loreman, & Forlin, 2012) before and after the course to determine if the course influenced their self-efficacy beliefs. Descriptive statistics and paired samples t-tests were used to analyze the data. The results indicated that the course had a significant, positive influence on preservice teachers’ self-efficacy beliefs toward teaching in an inclusive classroom. Discussion and implications of the findings as well as future research are examined.